Ablation of SP-A has a negative impact on the susceptibility of mice to Klebsiella pneumoniae infection after ozone exposure: sex differences - Mikerov Anatoly N; Haque Rizwanul; Gan Xiaozhuang; Guo Xiaoxuan; Phelps David S; Floros Joanna (Respiratory Research, 2008)
Abstract Background Surfactant protein A (SP-A) enhances phagocytosis of bacteria, including Klebsiella pneumoniae, by alveolar macrophages. Ozone, a major air pollutant, can cause oxidation of surfactant and may influence lung immune function. Immune function may also be affected by sex-specific mechanisms. We hypothesized that ablation of SP-A has a negative impact on the susceptibility of mice to Klebsiella pneumoniae infection after ozone exposure, and that sex differences in the effect of ozone do exist. Methods Male and female SP-A (-/-) mice on the C57BL/6J background were exposed to ozone or to filtered air (FA) used as a control and then infected intratracheally with K. pneumoniae bacteria. Survival rate was monitored during a 14-day period. In addition, protein oxidation levels and in vivo phagocytosis were checked 1 h after inoculation of PBS used as a sham control and after inoculation of K. pneumoniae bacteria in PBS, respectively. Results We found: 1) ozone exposure followed by K. pneumoniae infection decreases survival and alveolar macrophage phagocytic function of SP-A (-/-) mice compared to filtered air exposure (p < 0.05), and females are more affected than males; 2) SP-A (-/-) mice (exposed either to ozone or FA) are more susceptible to infection with K. pneumoniae than wild type (WT) mice regarding their survival rate and macrophage phagocytic function; the phagocytic function of FA SP-A(-/-) is similar to that of ozone exposed WT. 3) ozone exposure appears to increase infiltration of PMNs, total protein, and SP-A oxidation in WT mice; infiltration of PMNs and total protein oxidation appears to be more pronounced in female mice in response to ozone; 4) ozone exposure increases SP-A oxidation in WT females significantly more than in males. Conclusion Absence (i.e. ablation of SP-A in SP-A (-/-) mice) or reduction of functional activity of SP-A (i.e. oxidation of SP-A in WT mice) increases the susceptibility of mice to experimental pneumonia after ozone exposure, and in both cases females are more affected by ozone exposure than males.